A Three-dimensional Finite Element Analysis of Stress Distribution in Inclined Placed Implants - Emel Yurekli; Serhat Emre Ozkir (Mashhad University of Medical Sciences, 2020)
Introduction: Short implants are considered as a sole option in many patients due to anatomical limitations. It was aimed to assess the functional load stress at implants, surrounding bone and superstructures with different inclination angle. Methods: Seven finite element models with three implants (4 mm × 8 mm) and a separate model with longer implants (4 mm× 10 mm) with an angulation of 37° were designed. The implants were first placed vertically and then angled in distal direction preserving their parallelism increasing 6 ° at each step. Chromium-Cobalt was used to prepare superstructures. Oblique force of 100 N was applied on superstructures. Result: Inclined implant replacement did not significantly increase stress and compressive forces on bone, and the stress on implant surrounding bone decreased as inclination angle increased. On the other hand, in the model with linger implant more homogenous stress distribution was observed and implant's von Mises values ​​decreased. Conclusion: Inclination of implants could have no detrimental effects on bone. Furthermore, inclination of implants provides the opportunity of placing longer implants and also more favorable stress distribution around the implants and in bone.